Analisis Pelayanan Kefarmasian Berdasarkan Indikator Pelayanan Pasien WHO pada Puskesmas Kecamatan yang Belum dan Sudah Terakreditasi di Kota Depok - Makhdalena, Makhdalena; Jufri, Mahdi; Andrajati, Retnosari (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Pharmaceutical care based on WHO patient care indicators in various developing countries, including Indonesia, have not met the requirements. Puskesmas accreditation is expected to improve pharmaceutical care that has an impact on rational drug use. The purpose of the study was to analyze pharmacy care based on WHO patient care indicators in all sub-district health centers (9 health centers not yet accredited and 2 health centers already accredited) in Depok City. This study used a cross-sectional design and was carried out in December 2016-February 2017. The sample was adult patients from general poly and accompanying patients from integrated management of sick toddlers who met the inclusion criteria, as well as all prescription drugs taken. There were 30 respondents and 30 prescriptions for each sub-district health center. Data collection was done through interviews and observation of respondents and analysis of the recipe sheets. Data analysis used Mann-Whitney and Chi-square tests. The results show that the sub-district health centers have not been accredited which meets WHO recommendations for preparation time and delivery of drugs (> 3 minutes) of 77.8% and those who are 100% accredited. None of the sub-district health centers in Depok City meet WHO recommendations for the suitability of drug delivery, adequate drug labeling and patients with correct drug knowledge (= 100%). The time of preparation and delivery of drugs at the subdistrict health centers has been accredited significantly longer than those not yet accredited (p